Artificial Intelligence and Olfactory Cultural Heritage - Ramšak, Mojca (Od algoritma do prava: Pravni, ekonomski in kulturni izzivi umetne inteligence, 2025)
The chapter presents the use of artificial intelligence in the preservation and interpretation of olfactory cultural heritage. It discusses the main stages of technological progress, legal challenges and ethical issues that arise at the intersection of artificial intelligence and the olfactory aspect of cultural heritage. The analysis focuses on the potential of artificial intelligence for the digitisation, reconstruction and preservation of historical smells, as well as the ethical framework required to protect and manage this intangible heritage. The author also outlines insights into the future directions of development in this field and proposes guidelines for the design of measures that would enable the responsible and effective use of artificial intelligence in the context of olfactory cultural heritage.